Relasi Interaksi Pengguna Media Sosial Facebook terhadap Peningkatan Pengetahuan Agama - Eneng Humaeroh (Universitas Palangka Raya, 2023)
Facebook social media (social media) has a significant influence on interaction, this social media is one of the choices of social media users in sharing information both entertainment and other important information. Social media users use this platform to increase religious knowledge that can be easily accessed. This study tries to reveal how much the interaction variable on Facebook has an influence on the variable of increasing users' religious knowledge. This study was designed using a quantitative research approach that uses a percentage formula to obtain the magnitude or percentage of influence for users. The respondents of this study amounted to 20 people who were randomly selected from the population of Facebook social media users and took data sources for 2 weeks. The results showed significance between variables, namely 90% of interactions on Facebook influenced the increase in religious knowledge with 70% active users online every day. Other Jawabab given by respondents were 90% of users accessing general knowledge, 85% accessing entertainment, 75% accessing viral news, the rest of others amounting to 65%.